Genetics: Polymorphisms, Epigenetics, and Something In Between. (29th November 2011) - Maggert, Keith A.
Abstract : At its broadest sense, to say that a phenotype is epigenetic suggests that it occurs without changes in DNA sequence, yet is heritable through cell division and occasionally from one organismal generation to the next. Since gene regulatory changes are oftentimes in response to environmental stimuli and may be retained in descendent cells, there is a growing expectation that one's experiences may have consequence for subsequent generations and thus impact evolution by decoupling a selectable phenotype from its underlying heritable genotype. But the risk of this overbroad use of "epigenetic" is a conflation of genuine cases of heritable non-sequence genetic information with trivial modes of gene regulation. A look at the term "epigenetic" and some problems with its increasing prevalence argues for a more reserved and precise set of defining characteristics. Additionally, questions arising about how we define the "sequence independence" aspect of epigenetic inheritance suggest a form of genome evolution resulting from induced polymorphisms at repeated loci (e.g., the rDNA or heterochromatin).